Association of brain-derived neurotrophic factor levels at different trimesters and new-onset depressive symptom in the third trimester among pregnant women: a longitudinal study - Yue-rong Zhang; Ya-ping Liu; Xiang-mei Wu; Yuan Yan; Yan-feng Lou; Juan Ni (Frontiers in Psychiatry, 2025)
BackgroundAccumulating evidence e suggests that brain-derived neurotrophic factor (BDNF) may play a role in the development of depression. However, changes in serum BDNF during distinct gestational periods and their association with prenatal depression remain unclear.ObjectivesTo investigate the change of serum BDNF in the first, second and third trimester and their longitudinal association with depressive symptoms in the third trimester.MethodsDepressive symptoms in the first and third trimester were assessed using the Patient Health Questionnaire-9 (PHQ-9). An automatic biochemical analyzer was used to detect serum BDNF levels based on enzyme-linked immunosorbent assay (ELISA) in the first, second and third trimester. Linear regression, binary and multivariable logistic regression model were used to analyze the association between BDNF levels during different pregnancy with PHQ-9 score and depressive symptoms in the third trimester.ResultsThe mean age of 500 pregnant women included in this study was (26.8 ± 2.3) years in the first trimester. At the third trimester, a total of 72 pregnant women (14.4%) developed depressive symptoms. The average serum BDNF level was highest in the first trimester and lowest in the second trimester. Each 1 pg/mL increase of first trimester BDNF was associated with a 43% decrease in the risk of prenatal depressive symptoms (95% confidence interval [95% CI]: 0.51, 0.65); each 1 pg/mL increase of second trimester BDNF was a 39% decrease in the risk of prenatal depressive symptoms (95% CI: 0.54, 0.68); each 1 pg/mL increase of third trimester BDNF was associated with a 36% decrease in the risk of prenatal depressive symptoms (95% CI: 0.58, 0.71).ConclusionOverall, serum BDNF levels in the first, second, and third trimester were significantly associated with decreased PHQ-9 score and reduced risk of prenatal depressive symptoms. Serum BDNF shows promise as a predictive biomarker for antenatal depressive symptoms across all trimesters.